The health of women in the US fire service - Jahnke, Sara A (BioMed Central, 2012)
BACKGROUND: Despite statements from national fire service organizations, including the International Association of Fire Fighters (IAFF) and the International Association of Fire Chiefs (IAFC), promoting a diverse work force related to gender within the fire service, rates of women firefighters remain very low. Thus, research into why this extensive gender disparity continues is a high priority. Recent years have seen a number of large scale studies on firefighter health and health risk behaviors however, none have focused on the health of women firefighters and nearly all have eliminated women from the sample due to small sample size. Data from the present report is drawn from all females in a large, randomly selected cohort of firefighters in an epidemiological study designed to assess health outcomes and health risk behaviors identified as most important to the fire service. METHODS: Data reported for the present study were collected as baseline data for the Firefighter Injury and Risk Evaluation (FIRE) Study, a longitudinal cohort study examining risk factors for injury in both career and volunteer firefighters in the IAFC Missouri Valley Region. Of the departments assessed, only 8 career and 6 volunteer departments had any women firefighters. All the women solicited for participation chose to enroll in the study. The number of women ranged from 1 to 7 in career departments and 1 to 6 in volunteer departments. RESULTS: Where possible, comparisons are made between female firefighters and published data on male firefighters as well as comparisons between female firefighters and military members. Compared to male firefighters, females had more favorable body composition among both career and volunteer firefighters. Tobacco use rates were generally higher among females than males and rates among female firefighters were similar to the rates of female military members. While rates of alcohol use were higher than the general population, only one of the participants evidenced responses in the range of concern on the CAGE screening. CONCLUSIONS: In general, the findings offer an interesting glimpse of the health of women in the fire service as a generally healthy occupational workforce with some unique health risk behavior challenges. They also highlight some of the similarities and differences between male and female firefighters and bolster the argument for studying female firefighters as a unique occupational sub-population.